Pemanfaatan Buah Nangka Menjadi Manisan Di Desa Lawang Agung - Akhmad Fikri Fuzan; Afif Rizky Sadifatiasmi; Dina Mariana Parhusip; Fathul Syafiq Alfian; Heriska Febriani; M. Khalid Haikal Hosali; Nia Anggraini; Tasya Islami Desiani; Zelika Riananda Partiwi; Barika Barika (UNIB Press, 2023)
Jackfruit is a fruit that can be found easily in the village of Lawang Agung, Air Periukan District, Seluma Regency, Bengkulu Province. This research was conducted with the aim of fulfilling the assignment of a Real Work Lecture organized by the University of Bengkulu. With this program, it is hoped that it can help the natural resources in the village of Lawang Agung, Air Periukan District, Seluma Regency, Bengkulu Province. This is because the previous village program distributed jackfruit tree seeds to the local community. Jackfruit can be said to be an easy thing to find in the village of Lawang Agung. Therefore, it makes researchers move to carry out a work program with jackfruit as raw material. This was quite successfully done, the community accepted it positively because previously no one had thought of making jackfruit into a sweet. With this research, the people of Lawang Agung village can enjoy jackfruit in different ways and can be stored for a long time. This study uses descriptive qualitative research methods which use interview, observation and documentation techniques.